2006
DOI: 10.1586/14737175.6.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate for the treatment of epilepsy and other nervous system disorders

Abstract: Initially synthesized as an oral hypoglycemic agent, topiramate was approved for use as an anticonvulsant in 1996. Its broad spectrum efficacy in epilepsy, including as monotherapy and in children, is well established. Topiramate has also been used in the management of nonepileptic neurologic and psychiatric conditions, including migraine prophylaxis (with firmly established efficacy), obesity (with some evidence of long-term maintenance of weight loss), substance dependence, bipolar disorder and neuropathic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…As observed for sulphonamides, also sulphamates and sulphamides exert their inhibitory action through coordination to zinc ion and consequent substitution of the water molecule/ hydroxide ion 1 . Plenty of studies has been reported showing that many sulphamates possess effective inhibitory properties against all known human isoforms 1,11,[16][17][18][19] , with some derivatives, such as the sugar sulphamate topiramate (compound 1 in Figure 1), successfully used for the treatment of a variety of diseases such as epilepsy, migraine, and obesity 20,21 . Although the sulphamide group was initially considered not particularly suitable for obtaining potent CAIs 22 , several compounds containing a primary sulphamide moiety have also been proved to possess a high CA inhibition activity 1,11,19,23 .…”
Section: Introductionmentioning
confidence: 99%
“…As observed for sulphonamides, also sulphamates and sulphamides exert their inhibitory action through coordination to zinc ion and consequent substitution of the water molecule/ hydroxide ion 1 . Plenty of studies has been reported showing that many sulphamates possess effective inhibitory properties against all known human isoforms 1,11,[16][17][18][19] , with some derivatives, such as the sugar sulphamate topiramate (compound 1 in Figure 1), successfully used for the treatment of a variety of diseases such as epilepsy, migraine, and obesity 20,21 . Although the sulphamide group was initially considered not particularly suitable for obtaining potent CAIs 22 , several compounds containing a primary sulphamide moiety have also been proved to possess a high CA inhibition activity 1,11,19,23 .…”
Section: Introductionmentioning
confidence: 99%
“…[12] It is used to treat CNS conditions such as neuropathies, eating disorders, alcohol and drug dependence, migraine, nerve injury, restless leg syndrome, essential tremor and psychiatric diseases. [13][14][15] Topiramate is generally well tolerated at low doses [16] but at high doses it may cause various kinds of adverse effects including paraesthesia, dysphasia, fatigue, confusion and insomnia. [17] Topiramate is also used for the treatment of classical trigeminal neuralgia, but its efficacy remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, it bears no resemblance to previously used anticonvulsant agents and was originally synthesized as a chemical intermediate during a program to identify inhibitors of fructose-1,6-bisphosphatase as potential antidiabetic agents [87,88]. In combination with the sulfamate functionality, which appears to be essential for activity, many variations on the scaffold are tolerated.…”
Section: Topiramatementioning
confidence: 99%